Global challenges, Dutch solutions? The shape of responsibility in Dutch science and technology policies. Issue 3 (2nd September 2019) - van der Molen, Franke; Ludwig, David; Consoli, Luca; Zwart, Hub
ABSTRACT: The Netherlands has a well-established tradition of gearing science and technology to economic interests as well as societal and ethical concerns. This article outlines how national dynamics in the Netherlands have not only contributed to the adoption of Responsible Research and Innovation (RRI) frameworks but also to a distinctly Dutch meaning and institutionalization of responsibility. It identifies three core features of the Dutch context that have shaped this meaning and institutionalization: 1) a strong focus on the societal and economic relevance of research and innovation, 2) a political culture that emphasizes inclusive deliberation and collaboration, and 3) a focus on integration and synergy with respect to RRI. The integration of RRI in a collaborative system of companies, government and universities is embraced as contributing to a global leadership of the Netherlands in response to grand challenges. However, this integrative approach also limits the potential of Dutch RRI to function as a disruptive concept that challenges the status of interactions between science, technology, and society.